PEMERIKSAAN FUNGSI ENDOTEL PADA PENYAKIT KARDIOVASKULAR - Adhi Kurniawan; Mefri Yanni (HUMAN CARE JOURNAL, 2020)
Cardiovascular risk factors have been known to play a role in vascular endothelial damage. Endothelial damage can cause a condition called endothelial dysfunction. Endothelial dysfunction  is the initial process of various cardiovascular problems such as coronary heart disease, stroke, peripheral artery disease, and  others. Early stage endothelial damage can actually be detected, but often patients present at the stage of cardiovascular problems. Various examinations of endothelial function start from invasive, non invasive, until biomarkers marking the occurrence of dysfunction can be done. So that we can prevent or reduce the occurrence of further damage